2020
DOI: 10.1002/acr.23912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Birmingham Vasculitis Activity Score and the Five‐Factor Score to Assess Survival in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: A Study of 550 Patients From Spain (REVAS Registry)

Abstract: ObjectiveTo compare the accuracy of the Birmingham Vasculitis Activity Score (BVAS), version 3, and the Five Factor Score (FFS), version 1996 and version 2009, to assess survival in antineutrophil cytoplasmic antibody–associated vasculitis (AAV).MethodsA total of 550 patients with AAV (41.1% with granulomatosis with polyangiitis, 37.3% with microscopic polyangiitis, and 21.6% with eosinophilic granulomatosis with polyangiitis), diagnosed between 1990 and 2016, were analyzed. Receiver operating characteristic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
3
18
2
Order By: Relevance
“…They determined that only the fibrosis-4 index was associated with all-cause mortality during the follow-up in patients with MPA and GPA. BVAS and FFS are known to be useful to predict survival in antineutrophil cytoplasmic antibody-associated vasculitis and our results also support this finding [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…They determined that only the fibrosis-4 index was associated with all-cause mortality during the follow-up in patients with MPA and GPA. BVAS and FFS are known to be useful to predict survival in antineutrophil cytoplasmic antibody-associated vasculitis and our results also support this finding [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…PR3 ANCA positive 56%-83% 8,14 ANCA Negative 11%-31% 14,25 ENT involvement 70%-99% 13,26 Rhinologic Sinus involvement/Rhinitis 47%-72% 8,25 Recurrent epistaxis/nasal crusting 28%-83% 25,27 Nasal cavity adhesions 19%-26% 18,28 Rhinorrhoea 35%-54% 25,28 Mucosal ulcerations/granulations 10%-27% 18,28 Nasal septal perforation 8%-33% 27,29 External nasal/Saddle deformity 2%-22% 27,29 Epiphora 13% 29…”
Section: Prevalence Of Ent Features Of Granulomatosis With Polyangiitismentioning
confidence: 99%
“…Retro-orbital granulomata 3%-10% 25,29 Otologic Hearing loss (Audiometric) 23%-37% 8,28 OME/CHL 10%-31% 26,28 SNHL 8%-19% 26,30 Tinnitus 24%-30% 18,28 Head and neck/Laryngologic Hoarseness (including Laryngeal oedema/ Chronic laryngitis/VC palsy/Laryngeal ulceration)…”
Section: Prevalence Of Ent Features Of Granulomatosis With Polyangiitismentioning
confidence: 99%
See 1 more Smart Citation
“…They survey takes only a few minutes to complete but does require training and it is essential to only score acute/ongoing symptoms and signs, not fixed damage from vasculitis or comorbidity. The BVAS scoring system is the gold standard for assessing vasculitis disease activity in clinical trials and has been to shown to have prognostic value and correlate with mortality risk assessment [21,22]. It was hypothesized that this was not used routinely in clinical practice and this was confirmed since <20% had BVAS scores reported.…”
Section: Response Ratesmentioning
confidence: 99%